Life’s essential 8 and specific cancer risk and mortality in men and women: a population-based cohort analysis of 332,417 United Kingdom participants - Chuang Yang; Wenke Cheng; Patrick S. Plum; Florian Lordick; Jeanette Köppe; Ines Gockel; René Thieme (BMC Cancer)
Abstract Background This study aimed to explore the association between Life’s Essential 8 (LE8) and the risk of cancer occurrence and cancer-associated mortality across 24 cancer types. The cardiovascular health (CVH) score is constructed based on the overall LE8 score, providing a more direct measure of CVH and its potential relationship with cancer risk. Methods This cohort enrolled participants from a prospective cohort of the United Kingdom Biobank, including individuals aged 37–73 years, with 332,417 cancer-free participants. CVH scores were assessed using the LE8 metrics. The primary outcome of this study was the risk of cancer events, and the secondary outcome was cancer mortality. Competitive models were used to examine the associations between each 10-point increment in the CVH score and the outcomes, with stratified analyses conducted for both men and women to assess sex differences. Results The mean CVH score was 64.4(55.6,72.5) in men and 70.0 (61.2,78.1) in women (P < 0.001). During a mean follow-up time of 12.0 years, 12.32% (95% confidence interval [CI]: 12.21–12.43%) of participants developed cancer, and 2.13% (95% CI: 2.08–2.18%) died from cancer. A 10-point rise in CVH score was negatively associated with overall cancer occurrence in men (hazard ratio [HR]: 0.97, 95% CI: 0.96–0.98) and women (HR: 0.96, 95% CI: 0.95–0.97), along with reduced cancer mortality risk in both sexes. Moreover, sex differences were observed in the impact of a 10-point CVH increase on esophageal, gastric, colorectal, and liver cancers. Conclusions Lower CVH scores were associated with an increased overall cancer risk and higher cancer-related mortality, highlighting the need for cancer screening in patients with low CVH scores.